Need analysis of islamic Prophetic guidance and counseling for developing students' noble character - Santosa, Hardi; Prabowo, Agung Budi (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2022)
This study examines the need for an Islamic prophetic counseling development model. To achieve this goal, we used a mixed-method. The research subjects involved 244 students and four academic supervisors, and the research instruments were a noble character questionnaire and interview guidelines. Qualitative data were analyzed using the Miles and Huberman models, namely through data reduction, presentation, conclusion, and verification steps. While quantitative data were analyzed using descriptive analysis. The results of the study show: (1) there was no program designed in a systematic, comprehensive manner that touches the basic needs of students' moral development; (2) the ratios, content, and strategies in the ongoing guidance program had not met the standards and principles of guidance for all so that the process and objectives were not optimal; (3) there was a tendency for the behavior of some students to lead to moral decline; (4) understanding and practice of Islamic law as two determinant factors that affect the character of new students reached 27% and 16%; (5) the results of the student morality questionnaire showed that most (70.8%) were in the human category and (6) most of the students (97%) wanted a prophetic counseling model to develop noble character.